(untitled) (Perner’s Contacts, 2007)
The paper deals with calculation of influence of toll establishment on carriage in Czech Republic for domestic and foreign haulers. The outcome is just first and not very precise, because of small number of nodes (towns). Further will be this volume put more precisely via add of nodes. This work is very time-consuming. This paper can be something like manual for haulers how to count influence of toll establishment.